Effects of caffeine on inspiratory muscle function - Nicks, C. R.; Martin, E. H. (European Journal of Sport Science, 2020)
Research suggests that caffeine can enhance measures of muscular strength in the upper and lower extremities, although the literature is somewhat equivocal. Little is known on whether or not caffeine will improve maximal inspiratory pressure (MIP), a surrogate measure of inspiratory muscle strength. The purpose of the study was to determine the effects of a moderate dose of caffeine on inspiratory muscle function. Fifteen (8 male, 7 female) healthy adults (mean ± SD: age = 24.3 ± 6.4 years; height = 1.75 ± 0.11 m; body mass = 78.8 ± 16.5 kg) volunteered to participate in the study which used a double-blind, placebo-controlled, cross-over design. During the initial visit, baseline data was collected and participants were familiarized with inspiratory muscle measurements. For the second and third visits, participants ingested either a 5 mg kg-1 dose of caffeine (CAF) or placebo capsule (PL). After one hour, they completed at least 12 maximal inspiratory manoeuvres with 1 min rest between each attempt. MIP, maximal inspiratory peak pressure (PP), and maximal rate of pressure development (MRPD) were recorded. The CAF trial resulted in significantly higher MIP (154.7 ± 35.8 vs. 146.6 ± 37.6 cmH2O; p = 0.02) and PP (165.8 ± 36.8 vs. 158.3 cmH2O; p = 0.01) compared to the PL condition. No significant difference was observed in MRPD (p = 0.18). MIP and PP improved after ingestion of caffeine compared to the placebo condition. The findings from the study further establish caffeine`s potential ergogenic benefit on measures of muscular strength.